Aligning Technology and Strategy for Employee Development and Engagement in Non-Ergodic New Normal Environments: MNEs Operating in New Zealand - Ali, Faaizah (Auckland University of Technology, 2025)
This research examines how HR professionals in multinational enterprises (MNEs) operating in New Zealand perceive, evaluate, and implement human resources (HR) technologies for employee development and engagement in a volatile, non-ergodic new normal environment. Addressing empirical and contextual gaps in the literature, the research integrates the Technology Acceptance Model (TAM) with the dynamic capabilities framework to connect micro-level adoption cognitions with firm-level sensing, seizing, and transforming processes. Two questions guide the research: How do HR professionals in MNEs operating in New Zealand perceive and respond to the challenges and opportunities of the non-ergodic new normal environment, particularly in relation to using technology as a strategic asset toward employee development and engagement?; How do HR professionals evaluate and implement HR technologies, and to what extent do their decisions shape the development of sustained competitive advantage for the firm? A qualitative, phenomenological design was used. Semi-structured, in-depth interviews were conducted with seven HR professionals holding managerial roles across several industries within MNEs in New Zealand. Data was analysed inductively using thematic analysis. Findings show three perceived domains of opportunity: Technological development; Accessibility; and Instrumental gains. Perceived challenges are regarding: Contextual issues; And responsible innovation. Evaluation of HR technologies tends to be shaped by institutional influence, and personal use criteria, with adoption monitored through usage, qualitative feedback, and learning analytics. Sustainability of use depends on digital literacy, change management, and clear AI policies. Firms are centralising HR technology stacks, automating and streamlining routine tasks, and redeploying HR effort toward higher-value work, and prioritising future-proof, integrable systems. The integrated lens of the TAM and dynamic capabilities explains why user-centric ease of use and usefulness are necessary but insufficient, as HR technologies deliver strategic value when adoption is coupled with capability renewal. In New Zealand’s small-market context, successful initiatives prioritise usability, mobile access, security, and scalability over novelty, and balance global platform mandates with local responsiveness. The study contributes empirical depth to a literature dominated by reviews, advances a cross-level theoretical integration, and offers actionable guidance for HR leaders seeking technology-enabled agility, engagement, and capability building under persistent uncertainty.